Konsep Pendidikan Islam dalam Perspektif Ibnu Khaldun - Moh Nahrowi (FALASIFA : Jurnal Studi Keislaman, 2018)
Different ways of looking at the nature, purpose, methods and sources of Islamic education produce studies that are also different from one character to another, because each has a different flow, among others, religious-conservative schools, rational-religious flows and religious-instrumental religious flows. Ibn Kholdun, an instrumentalist-instrumentalist, has presented his views in the form of a general orientation in Islamic education, so he said that educational activities are not merely thoughts and reflections, but are social phenomena that are characteristic of human types, and must therefore enjoyed by every social being named human. In terms of educational curriculum, educational methods, and evaluations that are offered in their entirety, they deserve to be studied and examined, and if we look at each one of his views on the education curriculum, educational methods, and evaluations, which have been conceptualized by Ibn Khaldun almost from each sub-system in the Indonesian education system many are internalized. Keyword: The Concept of Islamic Education Ibn Khaldun